Gandhi's passion : the life and legacy of Mahatma Gandhi - Wolpert, Stanley, 1927-2019 (Oxford University Press, 2001)
"Wolpert chronicles the life of Mahatma Gandhi from his early days as a child of privilege to his humble rise to power and his assassination at the hands of a man of his own faith. This trajectory, like that of Christ, was the result of Gandhi's passion: his conscious courting of suffering as the means of reaching divine truth. From his early campaigns to end discrimination in South Africa to his leadership of a people's revolution to end the British imperial domination of India, Gandhi emerges as a man of inner conflicts conquered by his political genius and moral vision. Early influenced by nonviolent teachings in Hinduism, Jainism, Christianity, and Buddhism, he came to insist on the primacy of love for one's adversary in any conflict as the invincible power for change. He fearlessly courted suffering and imprisonment in pursuit of his moral vision. The sweet reasonableness of his "Great Soul," combined with the steel of his unyielding opposition to intolerance and oppression, would inspire India like no leader had since the Buddha - creating a legacy that would encourage Martin Luther King Jr., Nelson Mandela, and other global leaders to demand a better world through peaceful civil disobedience."--Jacket.